2016
DOI: 10.1098/rstb.2015.0333
|View full text |Cite
|
Sign up to set email alerts
|

Counting animal species with DNA barcodes: Canadian insects

Abstract: Recent estimates suggest that the global insect fauna includes fewer than six million species, but this projection is very uncertain because taxonomic work has been limited on some highly diverse groups. Validation of current estimates minimally requires the investigation of all lineages that are diverse enough to have a substantial impact on the final species count. This study represents a first step in this direction; it employs DNA barcoding to evaluate patterns of species richness in 27 orders of Canadian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
273
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(290 citation statements)
references
References 45 publications
12
273
0
5
Order By: Relevance
“…Diverse groups thought to contain many undescribed or unrecorded species included Acari, Hemiptera, Coleoptera (especially Staphylinidae), Lepidoptera (especially Tineoidea), and particularly Diptera and Hymenoptera. The question of arthropod diversity in Canada was revisited by Hebert et al (2016), who used results of DNA barcoding to reassess these earlier estimates. They concluded that there may be more than 100 000 species of insects in Canada, including as many as 50 000 species of Diptera and 30 000 species of Hymenoptera.…”
Section: The Prairies Ecozone and Its Constituent Ecoregionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diverse groups thought to contain many undescribed or unrecorded species included Acari, Hemiptera, Coleoptera (especially Staphylinidae), Lepidoptera (especially Tineoidea), and particularly Diptera and Hymenoptera. The question of arthropod diversity in Canada was revisited by Hebert et al (2016), who used results of DNA barcoding to reassess these earlier estimates. They concluded that there may be more than 100 000 species of insects in Canada, including as many as 50 000 species of Diptera and 30 000 species of Hymenoptera.…”
Section: The Prairies Ecozone and Its Constituent Ecoregionsmentioning
confidence: 99%
“…Comparison of the available checklists with predictions of total species richness from DNA barcoding studies (e.g., Hebert et al 2016, Sheffield et al 2017 shows that our knowledge of grassland arthropods is incomplete, except in the best-known taxonomic groups. Many checklists, including some of those summarised above, result from sampling brief windows of opportunity during the collecting season, perhaps as little as a few hours on one day of the year.…”
Section: The Arthropods Of Canadian Grasslands Initiativementioning
confidence: 99%
“…Barcode of Life) have produced big amount of data to populate BOLD's global database of DNA barcodes (Hendrich et al 2014, Morinière et al 2014, Hendrich et al 2015, Schmidt et al 2015, Hawlitschek et al 2016, Hebert et al 2016.…”
Section: Indobiosys -Dna Barcoding As a Tool For The Rapid Assessmentmentioning
confidence: 99%
“…Since then, taxonomic advances (including new molecular taxonomy tools) have improved the knowledge base for many groups. For example, Hebert et al (2016) used DNA barcoding to estimate more than 94 000 insect species in Canada, about a 58% increase over Danks (1979) estimate, with Diptera and Hymenoptera (especially Parasitica) being "unexpectedly diverse" and in general poorly known.…”
Section: Introductionmentioning
confidence: 99%